2001
DOI: 10.1111/j.1469-7793.2001.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of postexercise protein intake is important for muscle hypertrophy with resistance training in elderly humans

Abstract: 1. Age-associated loss of skeletal muscle mass and strength can partly be counteracted by resistance training, causing a net synthesis of muscular proteins. Protein synthesis is influenced synergistically by postexercise amino acid supplementation, but the importance of the timing of protein intake remains unresolved.2. The study investigated the importance of immediate (P0) or delayed (P2) intake of an oral protein supplement upon muscle hypertrophy and strength over a period of resistance training in elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
297
16
12

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(357 citation statements)
references
References 50 publications
(59 reference statements)
19
297
16
12
Order By: Relevance
“…Protein ingested soon after a resistance training session amplifies the resulting increase in muscle protein synthesis; the anabolic signal imparted by the exercise session is potentiated by leucine-mediated mTORC1 activation (Esmarck et al 2001;Breen and Phillips 2012;Burd et al 2012;Volek et al 2013). Hence, postexercise supplementation with 2-3 g of leucine (or ingestion of an equivalent amount from leucine-rich protein, such as whey), along with some carbohydrate to further enhance mTORC1 activity (via insulin), may have potential as an adjuvant to resistance training for prevention of sarcopenia.…”
Section: Dietary Leucine Promotes Anabolism By Stimulating Mtorc1 Actmentioning
confidence: 99%
“…Protein ingested soon after a resistance training session amplifies the resulting increase in muscle protein synthesis; the anabolic signal imparted by the exercise session is potentiated by leucine-mediated mTORC1 activation (Esmarck et al 2001;Breen and Phillips 2012;Burd et al 2012;Volek et al 2013). Hence, postexercise supplementation with 2-3 g of leucine (or ingestion of an equivalent amount from leucine-rich protein, such as whey), along with some carbohydrate to further enhance mTORC1 activity (via insulin), may have potential as an adjuvant to resistance training for prevention of sarcopenia.…”
Section: Dietary Leucine Promotes Anabolism By Stimulating Mtorc1 Actmentioning
confidence: 99%
“…The basic mechanism for excitationcontraction uncoupling is a larger number of ryanodine receptors uncoupled to dihydropyridine receptors [13]. In addition to the effects on muscle development, IGF-1 facilitates skeletal muscle dihydropyridine activity via tyrosine kinase-protein kinase C-dependent phosphorylation [14]. It has also been shown that IGF-1-dependent dihydropyridine modulation is impaired in aging skeletal muscles [60], which may explain, at least partially, the decline in muscle force with aging [53].…”
Section: Aging Considerationsmentioning
confidence: 99%
“…The results clearly showed that the net protein synthesis rate was significantly higher in the former than in the latter cases. Esmarck et al 45) demonstrated, using elderly subjects (around 74 years of age), that protein supplementation immediately after -as compared to that at 2-h after -resistance exercise was more effective in increasing muscle strength and muscle mass. Subjects participated in a 12-wk resistance training program (3 times per week) receiving oral protein in liquid form (10 g of protein, 7 g of carbohydrate, and 3 g of fat) immediately after, or at 2 h after, each training session.…”
Section: Regulation Of Protein Metabolism By Leucinementioning
confidence: 99%